A novel HLA‐A*02 variant, HLA‐A*02:575, detected in a Taiwanese bone marrow hematopoietic stem cell donor. Issue 6 (December 2015) - Yang, K. L.; Hung, J. H.; Lin, P. Y.
Abstract : One nucleotide substitution at residue 410 of HLA‐A*02:07:01 results in a new allele, HLA‐A*02:575 .